Men & Women Around The Messenger - Sa'ad Yusuf Abu ' Aziz (Darussalam, 2009)
the author has chosen one hundred personalities amongst the companions. he compiled narrations, hadist and incidences that contributed to the distinction of these individuals who have no similitude in the history of mankind afterthe prophets of Allah and His masengers. this is ibn mas'ud, mentioned. their excellence is further clearly established from the study of these individuals, their attributes and their characters with which they were embellished. for this reason, they were from the best of people ever raised up for mankind.